👤

117 a. (3x + 9) (4x − 2) = 0
b. (5x + 1) (3 -2x) = 0
Capacité 7, p. 91


Répondre :

Bonjour,

a) Produit de facteurs nuls :

3x + 9 = 0 ou 4x - 2 = 0

soit 3x = -9 ou 4x = 2

d'où x = -9/3 = -3 ou x = 2/4 = 1/2

b) Produit de facteurs nuls :

5x + 1 = 0 ou 3 - 2x = 0

soit 5x = -1 ou 2x = 3

d'où x = -1/5 ou x = 3/2

Bonsoir;

a. (3x + 9) (4x − 2) = 0

soit

3x+9=0

3x = -9

x = -9/3

x = -3

soit

4x-2 = 0

4x=2

x = 24

x = 1/2

x =0,5

b. (5x + 1) (3 -2x) = 0

soit

5x +1 = 0

5x = -1

x = -1/5

soit

3-2x = 0

3=2x

x= 3/2

x = 1,5